Streptomyces flavusporus sp. nov., a Novel Actinomycete Isolated from Naidong, Xizang (Tibet), China - Dan Tang; Xiaoxia Zhou; Haolin Qian; Yu Jiao; Yonggang Wang (Microorganisms)
The exploration of Streptomyces from extreme environments presents a particularly compelling avenue for novel compound discovery. A Gram-positive, pink-pigmented Streptomyces strain designated HC307T was isolated from a soil sample collected in Xizang (Tibet), China. The exploration of Streptomyces from extreme environments presents a particularly compelling avenue for novel compound discovery. In this study, the 16S rRNA sequence of strain HC307T exhibited the highest similarity with Streptomyces prasinosporus NRRL B-12431T (97.5%) and Streptomyces chromofuscus DSM 40273T (97.3%), which were below 98.7%. The draft genome of the bacteria was 10.0 Mb, with a G+C content of 70.0 mol%. The average nucleotide identity (ANI) values of strain HC307T and similar type strains ranged from 78.3% to 87.5% (<95%). The digital DNA-DNA hybridization (dDDH) values ranged from 22.6% to 33.9% (<70%), which was consistent with the results obtained from phylogenetic tree analysis. Phenotypically, this bacterium grew within the temperature range of 25–40 °C, at a pH range of 5 to 9, and in NaCl concentrations from 0% to 6% (w/v). The polar lipid profile of strain HC307T was diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and unidentified lipids. The analysis of 32 biosynthetic gene clusters (BGCs) indicated the strain’s capacity to synthesize diverse compounds. Phylogenetic and phenotypic analyses demonstrated that strain HC307T represented a novel species within the genus Streptomyces, and proposed the name Streptomyces flavusporus sp. nov., with strain HC307T (=DSM 35222T=CGMCC 32047T). The strain was deposited in Deutsche Sammlung von Mikroorganismen und Zellkulturen and the China General Microbiological Culture Collection Center for patent procedures under the Budapest Treaty.